MOTIVASI CHINA MELAKUKAN INVESTASI BIDANG TEKSTIL DI SPANYOL TAHUN 2003 – 2007 - Ifdal Yahya; Safri Harto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research explains the motivation of China to invest in the field of textile Spain 2003 – 2007. Foreign direct investment or Outward Direct Investment (ODI) is one of the goals of a country to cooperate with other countries in the form of developing a product to provide working capital to the country concerned. One of the countries that actively ODI to another country is China. Spain is one of the countries that cooperate with China in the field of textile. According to Nicolas and Thomsen, in 2006, Spain is the third largest recipient of Chinese ODI stock among all EU countries. The value of Chinese ODI investment increased rapidly expanding into Spain in 2006 and 2007 based on sources from the Ministry of Commerce (MOFCOM) of China Government.This study showed of China's motivation to invest in European countries including Spain in the field of textiles is to search for market share . Approximately 85 % indicated that the main reason for China's investment in the EU is to gain market share in Europe and to provide goods and services in the EU market. The Spanish government has been trying to attract investors to develop the area . One of the cities that are ready to accept investment is the City of Catalonia. There is strong evidence that Chinese ODI to Spain is inclined on one region (Catalonia) , although the investment option seems to be mostly driven on the basis of the existing network infrastructure and availability of domestic profits expatriate community in the region. Catalonia City has prepared himself by making programs including development of human resources in Catalunya and made strides improving the cultural and creative industries and sustainable development in Catalonia including the textile industry.Keywords : China, Spain, Catalonia, investment, textile, outward direct investment (ODI)